Dear supplier, how sustainable are you? - Iain J. Fraser; Martin Müller; Julia Schwarzkopf (Sustainability Management Forum, 2020)
This article analyses one of the most common tools employed by global focal companies in sustainable supply chain management (SSCM) across all industries: supplier sustainability self-assessment questionnaires. Extant research has moved beyond the questions of whether and which suppliers should be assessed. Current research is already focussing on how to share and standardise such assessment data. Despite mounting general research on SSCM, we identified that specific tools such as self-assessment questionnaires have not been empirically analysed in SSCM literature. Thus, this paper addresses the research questions of what differences there are among supplier self-assessment questionnaires and how supplier responses to such questionnaires might be influenced. Our research involves an abductive multiple-case study design and an analysis of over 25,000 responses from globally dispersed suppliers to two types of supplier sustainability self-assessment questionnaires administered and requested by a~global automotive focal company.Although the two questionnaires covered similar areas of sustainability practices and were administered to suppliers of the same focal company, the suppliers' responses demonstrated various observable differences in average sustainability scores.Social desirability bias and supplier assessment fatigue were identified as issues confronting such questionnaires. We find that questionnaire design, how the questionnaire is embedded in the focal company's processes and institutional settings are factors that potentially influence suppliers' responses and could counteract social desirability bias and supplier assessment fatigue. Based on these findings we make suggestions for improving these SSCM tools and provide recommendations for further research.
Keywords: 650; Sustainable supply chain management; Supplier assessment; Self-assessment; Sustainability assessment tools; Supplier assessment fatigue; Social desirability bias